2011
DOI: 10.1097/psy.0b013e318227a9bc
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality and All-Cause Mortality in Cardiac Patients-Data From a German Cohort Study

Abstract: In the present study, Type D personality and its constituents are not associated with increased mortality in patients with heart disease. The discrepancies with previous results deserve further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 54 publications
5
61
0
11
Order By: Relevance
“…The two larger studies conducted outside the Tilburg group [17,18] had analyzed Type D personality data using both the scoring procedure of the original investigator group, but also by preserving NA and SI as continuous variables and examining their interaction effect, and in neither instance found a significant bivariate or multivariate prediction of mortality. Could claims about Type D personality's independent prognostic value nonetheless be revived by reanalysis of the data from the earlier studies that preserved the continuous nature of component variables?…”
Section: Rescuing Type D Personality As An Interaction Term In a Regrmentioning
confidence: 99%
See 1 more Smart Citation
“…The two larger studies conducted outside the Tilburg group [17,18] had analyzed Type D personality data using both the scoring procedure of the original investigator group, but also by preserving NA and SI as continuous variables and examining their interaction effect, and in neither instance found a significant bivariate or multivariate prediction of mortality. Could claims about Type D personality's independent prognostic value nonetheless be revived by reanalysis of the data from the earlier studies that preserved the continuous nature of component variables?…”
Section: Rescuing Type D Personality As An Interaction Term In a Regrmentioning
confidence: 99%
“…The first one failed to find a prognostic value for Type D, but was underpowered to do so, with only 11 deaths being explained [16]. Then, another two more studies from outside the original investigator group were published, with larger numbers of deaths to be explained than most of the previous studies, but neither found evidence for a prognostic value of Type D personality in unadjusted or adjusted models, despite one having 172 deaths among 977 patients with CVD [17] and the other study having 192 deaths at 18 months follow-up of 706 HF patients [18]. Both of the studies relied on all cause, rather than cardiac-specific mortality as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Coyne et al [15] investigated the prognostic value of Type D on mortality in a large sample of Chronic Heart Failure (CHF) patients, and found that Type D did not predict mortality at 18-month follow-up. Similarly, Grande et al [16] found no association between Type D and allcause-mortality in a large sample of German cardiac patients at 6-year follow-up. These studies have the advantage over previous research on Type D in terms of their large samples.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, two large-scale studies [15,16] failed to find an association between Type D and mortality in cardiac patients. Coyne et al [15] investigated the prognostic value of Type D on mortality in a large sample of Chronic Heart Failure (CHF) patients, and found that Type D did not predict mortality at 18-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…These traits are thought to operate synergistically [39], and Type D cardiac patients have been found to be less adherent to cardioprotective medications, to view their heart condition more negatively, experience higher levels of depressive symptoms over time, and gain fewer benefits from CR [40][41][42][43][44]. While a number of meta-analyses have also shown Type D personality to predict worsened prognosis in persons with CHD [45,46], recent studies have failed to replicate these results [47][48][49][50], which has generated considerable critique. Critics of Type D highlight that the majority of these studies included small samples, were conducted by a single investigator group, and statistically analysed Type D personality as a dichotomized variable instead of an interaction term, thereby increasing the risk of spurious results [50][51][52].…”
Section: Anger and Hostilitymentioning
confidence: 86%